Circulating microRNA-451 as a predictor of resistance to neoadjuvant chemotherapy in breast cancer - Gu, Xi; Xue, Jin-Qi; Han, Si-Jia; Qian, Song-Ying; Zhang, Wen-Hai (Cancer biomarkers : section A of Disease markers, 2016)
OBJECTIVE: We aimed to explore the potential application of circulating microRNA-451 (miR-451) in serum in predicting the resistance to neoadjuvant chemotherapy (NACT) in breast cancer (BC). METHODS: Eighty-two BC patients who underwent NACT were recruited in our study, including 41 NACT-sensitive patients (NACT-sensitive group) and 41 NACT-resistant patients (NACT-resistant group). Additionally, 60 healthy subjects were selected as normal controls. Epirubicin-resistant MCF-7 BC cell line (MCF-7/EPI) and docetaxel-resistant MCF-7 BC cell line(MCF-7/DOC) were cultured in our study. MTT assay was applied to calculate the survival rates of MCF-7 cells, MCF-7/DOC cells and MCF-7/EPI cells. The expression levels of miR-451 in normal controls, NACT-sensitive group, NACT-resistant group, MCF-7 cells, MCF-7/DOC cells and MCF-7/EPI cells were measured by qRT-PCR method. RESULTS: The proliferation rates of both the MCF-7/DOC and MCF-7/EPI cells were significantly restrained at the drug concentration of 10 ng/ml, 50 ng/ml, 100 ng/ml and 200 ng/ml. However, the proliferation rates of MCF-7/DOC and MCF-7/EPI cells both increased significantly at the drug concentration of 500ng/ml. Furthermore, the IC50 of MCF-7/DOC cells was 23.603 ng/ml and the IC50 of MCF-7/EPI cells was 3.209 ng/ml. The relative expression of miR-451 was significantly lower in both the NACT-resistant group and the NACT-sensitive group than the normal control group. We also found that the relative expression level of miR-451 was significantly lower in the NACT-resistant group than that in the NACT-sensitive group. The expression of miR-451 in the MCF-7/EPI and the MCF-7/DOC cell lines was significantly lower than that in the MCF-7 cell lines. CONCLUSION: We supported the view that the relative expression level of miR-451 was lower in the NACT-resistant BC patients, suggesting the circulating miR-451 may have a functional significance in predicting the resistance to NACT in BC patients. We laid a foundation for further research on the resistance to NACT in BC treatment.